Optimization and H∞ Performance Analysis for Load Frequency Control of Power Systems With Time-Varying Delays - Su, Kangyou; Li, Yan; Chen, Jian; Duan, Wenyong (Frontiers in Energy Research, 2021)
With the development and expansion of the power grid, the load frequency control (LFC) scheme receives sensor signals and outputs control signals through an open communication network with a mass of data and extensive information exchange, which may introduce constant, and time-varying delays. This paper considers the optimization and H∞ performance problem for LFC of power systems with time-varying delays. Some improved criteria for guaranteeing the stability and H∞ performance of the closed-loop system with unknown external load disturbances via the Lyapunov stability theory application. An unique delay-dependent proportional-integral (PI) controller and an optimized PI controller are designed for a specified H∞ performance index and set, respectively. The criteria proposed in this paper are based on linear matrix inequalities (LMIs), which can be easily solved by the MATLAB LMI-Toolbox. Finally, in case studies, the effectiveness of our method is demonstrated.